Malawi : Economic Development Document. (IMF Staff Country Reports; Country Report ;, 2017)
This Economic development Document presents an overview of Malawi's Development Plan. Disappointing results with respect to implementation of Malawi Growth and Development Strategy II have triggered a qualified rethink in Malawi's development planning process. There is a growing recognition that Malawi needs a more realistic development plan, in terms of both the underlying assumptions and resource availability, as well as with fewer priorities and a greater emphasis on implementation. Climate change has also become a major new factor in this process. The recent formation of a quasi-independent National Development and Planning Commission is expected to help in improving the independence of the planning process in Malawi.